2018
DOI: 10.2139/ssrn.3301714
|View full text |Cite
|
Sign up to set email alerts
|

Blockchains = Less Government, More Market

Abstract: We provide a survey of blockchain's potential to propel private entrepreneurial discovery of institutions that challenge state hegemony. We introduce institutional cryptoeconomics, and then we describe blockchain as a technology that increases the opportunity set of entrepreneurial action. We then survey blockchain's potential to challenge state hegemony in five socioeconomic areas. We also discuss some implications of blockchainbased economic infrastructure for public policy and regulation. These contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Finally, any discussion of entrepreneurial discovery which challenge domains traditionally managed by the state (in the manner of Berg et al , forthcoming) should fully account for competing motivations. Fungible currencies are attractive to individual economic actors, owing both to their certainty in future use, as well as the privacy protections they offer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, any discussion of entrepreneurial discovery which challenge domains traditionally managed by the state (in the manner of Berg et al , forthcoming) should fully account for competing motivations. Fungible currencies are attractive to individual economic actors, owing both to their certainty in future use, as well as the privacy protections they offer.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the quality of money in its various guises is directly relevant to any comparative examination of monetary institutions. In this respect, discussions around privatised monetary institutions are not a recent phenomenon (see Hayek, ; Selgin, ; White, ), while more recent technological innovations add extra impetus to this question of competition with fiat currency (Berg et al , forthcoming). This is a neglected topic, as much of the literature concerning the theory of money focuses on quantitative, rather than qualitative aspects (see Bagus, , ).…”
Section: Fungibility Criteria and The Quality Theory Of Moneymentioning
confidence: 99%
“…Among the potential impacts from the results obtained (Figure 4), it is demonstrated that the use of Blockchain leads to improvements in data storage, which could result in the reduction of bureaucratic processes, speeding up data processing and allowing, for example, the use of smart contracts. Furthermore, Blockchain is an important tool for sharing information such as clinical pathological data, drug distribution and supply chain stages of a wide number of products, contributing to more efficient surveillance and control (Abelseth, 2018;Atzori, 2018;Berg et al, 2018;Buth et al, 2019;Engin & Treleaven, 2019;Johnson, 2019;Kossow, 2019;Li et al, 2019;Marchionni, 2018;Thakur et al, 2019;Tseng et al, 2018).…”
mentioning
confidence: 99%
“…The identification that Blockchain would impact on the facilitation of direct democracy and data transparency was verified based on the possibility of offering a new mechanism for the construction of public policies and social participation, considering the possibility of reliable electronic elections (Berg et al, 2018;Lander & Cooper, 2017). By making use the distributed network, it would be possible to improve the reliability and ease of communication between the actors involved, allowing a bottomup model of organized and efficient public policy making (Ducas & Wilner, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation